Demographics and anthropometrics impact benefits of health intervention: data from the Reduce Obesity and Diabetes Project - L. Ostrowski; P. W. Speiser; S. Accacha; L. Altshuler; I. Fennoy; B. Lowell; R. Rapaport; W. Rosenfeld; S. P. Shelov; S. Ten; M. Rosenbaum; the ROAD Group (Wiley, 2019)
Summary Objective To determine the efficacy of a 4‐month school‐based health, nutrition and exercise intervention on body fatness and examine possible effects of demographic and anthropometric covariates. Methods Height, weight, waist circumference and body composition were measured in a diverse population of 644 NYC middle school students (mean ± SD age 12.7 ± 0.9 years; 46% male; 38% Hispanic, 17% East Asian, 15% South Asian, 13.5% African American, 8.5% Caucasian, 8% other) during the fall and spring semesters. Year 1 participants (n = 322) were controls. Experimental participants (year 2, n = 469) received a 12‐session classroom‐based health and nutrition educational programme with an optional exercise intervention. Results Groups were demographically and anthropometrically similar. The intervention resulted in significant reductions in indices of adiposity (ΔBMI z‐scores [−0.035 ± 0.014; p = 0.01], Δ% body fat [−0.5 ± 0.2; p < 0.0001] and Δwaist circumference [−0.73 ± 0.30 cm; p < 0.0001]). Intervention effects were greater (p = 0.01) in men (ΔBMI z‐score = −0.052 ± 0.015) versus women (0.022 ± 0.018), participants who were obese (ΔBMI z‐score −0.083 ± 0.022 kg m−2) versus lean (−0.0097 ± 0.020 kg m−2) and South Asians (Δ% body fat −1.03 ± 0.35) versus total (−0.49 ± 0.20%) participants (p = 0.005). Conclusion A 4‐month school‐based health intervention was effective in decreasing measures of adiposity in middle school students, particularly in men, participants who were obese and South Asians.